2010
DOI: 10.1152/physiolgenomics.00092.2010
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring mutations in the canine CFTR gene

Abstract: Naturally occurring cystic fibrosis (CF)-causing mutations in the CFTR gene have not been identified in any nonhuman animal species. Since domestic dogs are known to develop medical conditions associated with atypical CF in humans (e.g., bronchiectasis and pancreatitis), we hypothesized that dogs with these disorders likely have a higher expression rate of CFTR mutations than the at-large population. Temporal temperature-gradient gel electrophoresis (TTGE) was used to screen canine CFTR in 400 animals: 203 dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Since the partial (31) and complete (33) sequencing of the canine genome there has been considerable interest in the use of single nucleotide polymorphisms (SNPs) to help explain the ancestry and evolutionary origins of the domestic dog (Canis lupus familiaris) (33,53), as well as the phenotypic diversity between breeds (9). Moreover, as exemplified by recent studies (30,46), there is continual interest in identifying SNPs associated with breed-specific disorders to determine the causes of such disorders in dogs and to help elucidate the mechanisms involved in similar disorders within humans. One study that supports this approach has been a genome--wide association analysis, which identified a SNP within the gene coding canine Cu/Zn SOD in breeds susceptible to degenerative myelopathy (3); a disease similar to amyotrophic lateral sclerosis in humans, which is also associated with SNPs in the gene coding human Cu/Zn SOD (43).…”
Section: Introductionmentioning
confidence: 99%
“…Since the partial (31) and complete (33) sequencing of the canine genome there has been considerable interest in the use of single nucleotide polymorphisms (SNPs) to help explain the ancestry and evolutionary origins of the domestic dog (Canis lupus familiaris) (33,53), as well as the phenotypic diversity between breeds (9). Moreover, as exemplified by recent studies (30,46), there is continual interest in identifying SNPs associated with breed-specific disorders to determine the causes of such disorders in dogs and to help elucidate the mechanisms involved in similar disorders within humans. One study that supports this approach has been a genome--wide association analysis, which identified a SNP within the gene coding canine Cu/Zn SOD in breeds susceptible to degenerative myelopathy (3); a disease similar to amyotrophic lateral sclerosis in humans, which is also associated with SNPs in the gene coding human Cu/Zn SOD (43).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one explanation for discrepancy between CFTR inhibition potencies in T84 and MDCK cells is the differences in steviol's binding sites between human CFTR expressed in T84 cells and canine CFTR expressed in MDCK cells. In support of this notion, the amino acid sequences in the membrane-spanning domains of CFTR in human, mouse, rat, and dog, are different [36], [37]. CFTR inhibitors, such as CFTR inh -172, glibenclamide and GlyH-101 have been found to exert their inhibitory effects differently on several CFTR orthologs because of differences in inhibitor-binding sites for each compound [38].…”
Section: Discussionmentioning
confidence: 96%
“…We found that incubation with forskolin doubled the area of canine jejunal enteroids after 4 hours, indicating the presence of functional CFTR chloride channels, similar to human intestinal colonoids [13]. Thus, the forskolin-swelling CFTR function assay with canine enteroids has translational applications in drug screening, especially given that dogs have naturally occurring CFTR mutations similar to humans [13, 61].…”
Section: Discussionmentioning
confidence: 99%